2016
DOI: 10.1016/j.mgene.2016.03.007
|View full text |Cite
|
Sign up to set email alerts
|

MMP3 and TIMP2 gene variants as predisposing factors for Achilles tendon pathologies: Attempted replication study in a British case–control cohort

Abstract: Variants within the MMP3 (rs679620) and TIMP2 (rs4789932) genes have been associated with the risk of Achilles tendon pathology (ATP) in populations from South Africa and Australia. This study aimed to determine whether these variants were associated with the risk of ATP in British Caucasians. We recruited 118 cases with ATP, including a subset of 25 individuals with Achilles tendon rupture (RUP) and 131 controls. DNA samples were isolated from saliva and genotyped using qPCR. For the TIMP2 rs4789932 variant w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 28 publications
1
35
0
Order By: Relevance
“…Our findings concerning the role of MMP3 variant in shoulder tendinopathy is in part supported by findings in Achilles tendinopathy . In addition, another variant of MMP3 (rs3025058) was previously associated with the risk of RCT .…”
Section: Discussionsupporting
confidence: 87%
“…Our findings concerning the role of MMP3 variant in shoulder tendinopathy is in part supported by findings in Achilles tendinopathy . In addition, another variant of MMP3 (rs3025058) was previously associated with the risk of RCT .…”
Section: Discussionsupporting
confidence: 87%
“…In a case-control cohort of white British patients, El Khoury et al 23 found no significant differences in MMP3 SNP rs679620 between those with Achilles tendinopathy and controls. When the population was grouped by sex, the variation did reach significance: MMP3 rs679620 within the male population had an overrepresentation of the AG genotype in control patients ( P = .046) and the GG genotype in the rupture group ( P = .009; OR, 3.3; CI, 1.4-8.2).…”
Section: Resultsmentioning
confidence: 97%
“…81 In a case-control study using Australian and South African populations, El Khoury et al 22 found that TIMP2 rs4789932 SNP was significantly associated with Achilles tendinopathy risk, with overrepresentation of the CT genotype in patients with tendinopathy ( P = .004; OR, 1.77; CI, 1.2-2.6). In a follow-up study using 118 patients with Achilles injuries (93 tendinopathy, 25 rupture) and 131 white British participants, El Khoury et al 23 again linked differences in TIMP2 rs4789932 SNP with Achilles tendon injury ( P = .038). However, a different genotype, CC instead of CT, was overrepresented in tendinopathy patients ( P = .012; OR, 2.5; CI, 1.2-5.1) compared to controls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MIR608 rs4919510 polymorphism is associated with chronic AT ( p  = 0.023, OR = 1.6, 95%CI 1.1–2.5).Brown et al (2016) [36]Retrospective case-control study/4112 (87 AT and 25 RUP)/130 CONCON, 41.6 ± 11.6 (123); ATP, 43.9 ± 13.8 (112)CON, 63.1% M, 36.9% F; ATP, 60.7% M, 39.3% FCON, 25.9 ± 4.5 (123); ATP, 26.0 ± 4.0 (82)0Not specified, physically active peopleAs per Mokone et al (2005)Three inferred allele combinations constructed from COL5A1 rs12722, rs3196378 and rs71746744 increase risk of ATP, RUP and AT ( p  = 0.023, p  = 0.011, p  = 0.011). One inferred allele combination constructed from CASP8 rs3834129 and rs1045485 was significantly associated with an increased risk of AT ( p  = 0.031).El Khoury et al (2016) [38]Retrospective case-control study/4118 (93 AT and 25 RUP)/130 CONCON, 41.7 ± 11.6 (124); ATP, 43.7 ± 13.8 (117)CON, 62.6% M, 37.4% F; ATP, 60.2% M, 39.8% FCON, 25.9 ± 4.5 (123); ATP, 26.3 ± 4.1 ( n  = 86)0Not specified, physically active peopleAs per Mokone et al (2005) TIMP2 rs4789932 variant is associated with ATP in males ( p  = 0.038). MMP3 rs679620 variant is associated with RUP ( p  = 0.021).El Khoury et al (2015) [35]Retrospective case-control study/4135 (60 AUS + 75 SA)/239 (143 AUS + 96 SA)CON, 38.2 ± 11.2 (230); AT, 40.1 ± 14.2 (129)CON 50.6% M, 49.4% F; AT, 77.4% M, 22.6% FCON 24.2 ± 3.6 (235); AT 25.7 ± 3.9 (124)0Running, high-impact sportsAs per Mokone et al (2005) FBN2 rs331079 variant is associated with ATP in males ( p  = 0.035).No association between ELN rs2071307 variant and ATP ( p  = 0.795).El Khoury et al (2013) [24]Retrospective case-control study/4165 (59 AUS + 114 SA)/248 (152 AUS + 96 SA)AUS CON, 38.5 ± 11.9 (149); SA CON, 37.1 ± 10.0 (91); AUS ATP, 40.3 ± 14.1 (58); SA ATP, 40.2 ± 12.3 (107)AUS CON, 39.7% M, 60.3% F; SA CON, 66.3% M, 33.7% F; AUS ATP, 67.8% M, 32.2% F; SA ATP, 73% M, 27% FAUS CON 24.8 ± 4.0 (150); SA CON 23.3 ± 2.8 (93); AUS ATP 26.6 ± 4.1 (57); SA ATP 26.0 ± 3.9 (103)20 ControlsLong distance running, squashAs per Mokone et al (2005) TIMP2 rs4789932 variant is associated with ATP in combined SA and AUS populations (p = 0.016, OR = 1.58, 95% CI 1.03–2.43)None of the selected variants within the ADAMTS2 , ADAMTS5 , ADAMTS14 and ADAM12 genes were associated with risk of ATP in the two populations investigated ( p  = 0.316, p  = 0.323, p  = 0.849, p  = 0.633, respectively).Gaida et al (2009) [43]Cross-sectional study/360/60CON, 47 ± 10; AT, 48 ± 9CON, 53% M, 47% F; AT 53% M, 47% FCON, 25 ± 3; AT, 25 ± 30Not specifiedIndividuals with chronic Achilles tendon pain were diagnosed with midportion Achilles tendinopathy were included in the study.AT subjects showed evidence of underlyin...…”
Section: Resultsmentioning
confidence: 99%